Fluid management in haemodialysis: Conventional versus Body Composition Monitoring (BCM) supported management of overhydrated patients - Ponce,Pedro (2014)
Introduction: Normohydration is an important target in dialysis patients. In this study, we compared the performance of a bioimpedance spectroscopy device versus conventional clinical judgment in assessing the hydration status of HD patients and determining their ideal weight. Materials and Methods: 189 HD patients on online haemodiafiltration participated in this prospective, controlled, multicentre study. Dialysis units were randomly divided into an open-access and a blinded BCM group. Hydration status, blood pressure, weight gain, morbidity and mortality were assessed. Results: At baseline, 92 patients of the BCM-open group and 79 patients of the BCM-blinded group were overhydrated by ~3.8L. After one year, the rate of patients with OH > 2.5L was reduced to 52.5% in the open, and to 65.9% in the blinded group. Hospitalization and survival rate was not significantly different between the two groups. Conclusion: Results suggest that BCM is a helpful tool in supporting the fluid management of HD patients.